BENTUK-BENTUK REINFORMENT MELALUI METODE TANYA JAWAB DALAM PEMBELAJARAN AGAMA HINDU DAN BUDI PEKERTI SISWA DI SEKOLAH DASAR SD NEGERI 2 KEMENUH - Ni Ketut Aprilia; Ni Wayan Arini; Ni Made Muliani (PT. Hasba Edukasi Mandiri, 2026)
In the classroom learning process related to Hinduism and Character Education, teachers can apply the question-and-answer method. This method can stimulate students to train and develop their thinking skills, including memory. The question-and-answer method can also develop students' courage and skills in answering and expressing opinions. Based on this assumption, this research was conducted with a focus on the problem aspect, namely what forms of reinforcement are provided through the question-and-answer method in teaching Hinduism and Character Education to fourth-grade students at SD Negeri 2 Kemenuh. This research used qualitative methods. The basis of analysis was Oemar Hamalik's Behaviorist Theory. Data for this study were collected through observation, in-depth interviews, literature review, and documentation. Based on this review and analysis, the following assumptions can be made Effective forms of reinforcement should be implemented during learning and should be appropriately portioned, not too little, not too much, and not monotonous. There are certain times when teachers provide verbal, non-verbal, or incomplete reinforcement. This must, of course, be tailored to the characteristics and conditions of the students at the time. In every lesson, teachers are required to be active and creative in managing learning, as well as providing reinforcement skills.